To find how many zeros the function \( f(x) = x(x - 1)(2x + 4)^2 \) has, we need to analyze each factor of the function for its zeros.
-
The factor \( x \):
- This factor gives us a zero at \( x = 0 \) (with a multiplicity of 1).
-
The factor \( x - 1 \):
- This factor gives us a zero at \( x = 1 \) (with a multiplicity of 1).
-
The factor \( (2x + 4)^2 \):
- To find the zeros, we set \( 2x + 4 = 0 \).
- Solving this gives \( 2x = -4 \) or \( x = -2 \).
- The square indicates that this zero has a multiplicity of 2.
Now we can count the total number of zeros:
- From \( x \) : 1 zero (at \( x = 0 \))
- From \( x - 1 \): 1 zero (at \( x = 1 \))
- From \( (2x + 4)^2 \): 2 zeros (at \( x = -2 \), counted twice due to the square)
So the total number of zeros, including repeated zeros, is: 1 (from \( x \)) + 1 (from \( x - 1 \)) + 2 (from \( (2x + 4)^2 \)) = 4 zeros.
Thus, the correct response is:
4.